The Never Given 2022 Pittendrigh/Aschoff Lecture: The Clock Network in the Brain-Insights From Insects. - Helfrich-Förster, C. (Journal of Biological Rhythms, 2025)
My journey into chronobiology began in 1977 with lectures and internships with Wolfgang Engelmann and Hans Erkert at the University of Tübingen in Germany. At that time, the only known animal clock gene was Period, and the location and organization of the master circadian clock in the brain was completely unknown for the model insect Drosophila melanogaster. I was thus privileged to witness and participate in the research that led us from discovering the first clock gene to identifying the clock network in the fly brain and the putative pathways linking it to behavior and physiology. This article highlights my role in these developments and also shows how the successful use of D. melanogaster for studies of circadian rhythms has contributed to the understanding of clock networks in other animals. I also report on my experiences in the German scientific system and hope that my story will be of interest to some of you.